The results of Latarjet procedure under arthroscopy control - Golovakha, Maxim; Kuznietsov, Bohdan (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Latarjet procedure is one of the relevant techniques for the anterior and antero-inferior type of recurrent instability at the shoulder joint with a defect of the articular surface of the glenoid. A deeper study requires arthroscopic modification of this operation to assess its clinical effectiveness. Objective: to conduct a comparative analysis of open and arthroscopic Latarjet procedure, to evaluate intraoperative and postoperative complications and side effects of this surgical technique. Methods: a prospective randomized study was conducted, which included 30 patients: after open Latarjet procedure — 16 (53.3 %), arthroscopic — 14 (46.7 %). The results were evaluated at 3 and 6 weeks, 3–4 and 6–9 months after the operation using x-ray methods, computed tomography, Walch-Duplay and Rowe scales, and intraoperative and postoperative complications were also analyzed. In the case of arthroscopic technique, an increase in the volume of external rotation during the adduction and abduction of the shoulder, an open technique — a decrease (p = 0.01). A decrease of the volume during internal rotation (spinous process) was revealed with the use of both techniques, but with better results after arthroscopic (p = 0.02). Conclusions: when using arthroscopic and open methods of Latarjet procedure, a statistically confirmed equal improvement in results is observed with recurrent instability of the shoulder joint. The results indicate the clinically significant advantages of restoring the function of the shoulder joint, especially external rotation when using the arthroscopic technique of Latarjet procedure in comparison with the open technique.